Isolated and Combined Effect of Fartlek and Weight Training with Pranayama Practice on Selected Physiological Variables among Football Players - Mr.A.Robinson, Dr.A.Mahaboobjan, Mr.B.Andrew, Mr.S.Sathyanarayanan, Mrs.R.Yoganandhini (South Eastern European Journal of Public Health, 2025)
Introduction: Fartlek training is a kind of running training which involves random variations in speed and intensity. A Fartlek workout allows the body to adapt to using both sources of energy, with the desired adaptation towards fat metabolism occurring during slower periods. Weight training is known as resistance or strength training, builds lean, stronger muscles, strengthens the bones and joints, help to improve the muscle mass and mobility, as well as improve psychological wellbeing. Yogic practices, which aim at physical and mental self culture, have convincing scientific bases and produce consistent physiological changes. It has been reported that yogis are capable of remarkable feats of endurance and controlling their autonomic functions. Objectives: The study's goal was to determine the isolated and combined effects of fartlek and weight training with pranayama practice on selected physiological variables among football players. Methods: For that accomplish, sixty (60) college-level men football players were chosen at random from various colleges affiliated with Anna University in and around Coimbatore, Tamil Nadu, India. They ranged in age from 18 to 22. They have been split into 4 categories of fifteen students each. Specifically, group I trained on fartlek with pranayama, group II trained on weight with pranayama, group III combined fartlek and weight training with pranayama and group IV did not participate in any specific training session and acted as the control group. Before and after the training session, they underwent two tests. For six weeks, the study's training phase consisted of three alternate days each week. The physiological variables like vital capacity, systolic blood pressure and diastolic blood pressure was selected as criterion variables. A spirometer was used to measure vital capacity in liters per second, and a digital heart rate/blood pressure monitor was used to measure blood pressure in millimeters per hour. A few selected dependent variables were used to assess subjects in each of the four groups before and right after the training program. The difference was ascertained using the dependent "t" test, and the percentage change was also calculated. The groups were examined for significant differences using the analysis of covariance (ANCOVA). The 0.05 level of confidence was used for the hypothesis. For the hypothesis, the 0.05 level of confidence was selected. Conclusions: The isolated as well as combined effects of fartlek and weight training with pranayama practice on chosen physiological variables of football players resulted in a substantial change.